Implementation of Family Nursing Care for Clients with Rheumatoid Arthritis to Physical Mobility Disorders with Active and Passive Movement Exercises - Kumalasari, Intan; Oktaviani, Eva; Wahyudianto, Tri Agus (Journal of Applied Nursing and Health, 2023)
Background: Rheumatoid Arthritis (RA) is a disease characterized by a chronic autoimmune inflammatory disorder or autoimmune response that causes weakening of the joints and synovial lining, especially in the hands, feet, and knees. Patients with RA often experience impaired physical mobility, a condition where a person cannot move freely due to conditions that hinder movement (activity). One of the interventions that can be given to RA patients is Range of motion (ROM) exercises, which are exercises performed to maintain or improve the perfection of the ability to move joints normally and completely to increase muscle mass and muscle tone. research to assess the effectiveness of implementing family nursing care with active and passive movement exercises against impaired physical mobility in Rheumatoid Arthritis sufferers in the work area of Taba Health Center, Lubuklinggau City, in 2022. Methods: This study uses a qualitative design with a case study approach to describe information descriptively. In-depth and explores nursing problems for families with rheumatoid arthritis with impaired physical mobility due to joint stiffness. Results: After implementation by giving active and passive motion exercises to both subjects (Mr. S and Mrs. E) for five consecutive days with a time of 10-15 minutes, both subjects said that stiffness in the extremities was reduced and the value of muscle strength increased to 5 and 4. Conclusion: Implementing nursing care with active and passive motion exercises can increase joint strength in clients with rheumatoid arthritis.